Effect of Two Different Superstrate Layers on Bismuth titanate (BiT) array antennas - Al-Amani, Umar; F.H. , Wee; F., Malek; Farid, Ghani (2014)
The microwave industry has shown increasing interest in electronic ceramic material (ECM) due to its advantages, such as light weight, low cost, low loss, and high dielectric strength. In this paper, simple antennas covered by superstrate layers for 2.30 GHz to 2.50 GHz are proposed. The antennas are compact and have the capability of producing high performance in terms of gain, directivity, and radiation efficiency. Bismuth titanate with high dielectric constant of 21, was utilized as the ECM, while the superstrate layers chosen included a split ring resonator and dielectric material. The superstrate layers were designed for some improvement in the performance of directivity, gain, and return loss. The proposed antennas were simulated and fabricated. The results obtained were small antennas that possess high gain and high directivity with 3606, omni-directional signal transmission that resonant types of conventional dipole antenna cannot achieve. The gain of the antenna with the superstrate layer was enhanced by about 1 dBi over the antenna without a superstrate layer at 2.40 GHz.